Sub Urban : Perubahan Lingkungan Sebagai Inspirasi Pada Karya Seni Lukis - Putri, Malena Wati; Ramli, Zaenudin; Avianto, Joko Dwi (ATRAT: Jurnal Seni Rupa, 2024)
Sub urban is an interaction zone between villages and cities on the outskirts of the city around the main urban center. This Sub urban area is a source of inspiration for the author in creating this work of art, because the increasing number of land clearing for commercial, industrial and residential buildings in Indonesia, especially in areas near the author’s residence, is also an inspiration for this painting. This painting is a form of the author’s concerns and hopes for the sub urban environment so that development can run in balance with environmental conservation. This painting consists of 3 canvases which are presented as one triptych canvas. Overall, it presents the sub urban environment with its elements, and also indirectly in the three canvases depicts changes in the sub urban environment. This painting uses the technique of broken color impressionism. Impressionism has the value of transition, change, momentaryness which is in line with the concept of this painting. Small streaks of color, side by side, pile up on the canvas that blend optically when viewed from afar. The colors used are also bright and contrasting colors. This work offers a new contribution in the context of contemporary painting by combining the classic style of Impressionism with modern themes about the changing sub urban environment.